Large neck metastasis with unknown primary tumor: A case report - Dimitrijević Milovan; Bukurov Bojana; Jotić Ana (Vojnosanitetski Pregled)
Introduction. Metastatic head and neck carcinoma (HNC) from an unknown primary tumor is defined as a metastatic disease in the neck’s lymph nodes without evidence of a primary tumor after appropriate investigation. Multiple national guidelines recommend taking essential steps in diagnostic protocols which involve a detailed clinical exam with radiological imaging, fine-needle aspiration (FNA) biopsy of the cervical tumor, esophagogastroduodenoscopy (EGD) with palatine and lingual tonsillectomy, immunohistochemical staining, and human papillomavirus (HPV) detection. Treatment of HNCs of unknown primary origin involves surgery (neck dissection) with radiotherapy (RT), while some authors recommend chemo-radiotherapy in cases of advanced regional disease. Case report. A 44-year-old male was referred to the tertiary medical center because of a large ulcero-infiltrative cervical mass on the right side. Examination of the head and neck and flexible nasopharyngolaryngeal endoscopy was conducted, followed by computed tomography (CT) of the head, neck, and thorax with intravenous contrast. The primary localization of the tumor was not confirmed by these diagnostic methods. An open biopsy of the neck mass established a histopathology diagnosis of metastatic squamous cell carcinoma (SCC). Results of EGD with biopsies and bilateral tonsillectomy were negative for malignancy. Treatment included extended radical neck dissection with reconstruction and postoperative ipsilateral RT. The patient presented with an extensive pharyngolaryngeal tumor five years after the first surgery. Biopsy with histopathology examination confirmed the diagnosis of SCC. Conclusion. A structured step-by-step diagnostic approach to identifying the primary site of the metastatic HNC is mandatory. Substantial advances in diagnostics and operative techniques have increased the likelihood of primary tumor identification and detection of the disease's regional and systemic spread. The purpose of adherence to guidelines results in higher overall survival and longer regional disease-free survival in these patients.